2015
DOI: 10.1039/c5py00945f
|View full text |Cite
|
Sign up to set email alerts
|

Linear-selective cross-coupling polymerization of branched oligothiophene by deprotonative metalation and cross-coupling

Abstract: Brominated oligothiophene with a branched structure was subjected to deprotonative metalation with a bulky magnesium amide chloromagnesium 2,2,6,6-tetramethylpiperidine-2-yl lithium chloride salt (TMPMgCl·LiCl), which is known as the Knochel-Hauser base. The thus metalated oligothiophene was polymerized in the presence of a nickel(II) NHC (N-heterocyclic carbene) complex to afford polymers of M n of 4400 to 44 000, which corresponds well with the monomer feed/catalyst loading ratio. Analysis by MALDI-TOF MS su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…It was revealed that Murahashi coupling polymerization was successfully achieved by the lithiated species of chlorothiophene, which is prepared by treatment of n BuLi and 5 . Following addition of nickel catalyst 20 underwent polymerization, where use of CPME (cyclopentyl methyl ether) as a solvent was found effective . Block copolymerization was also shown to take place suggesting that the polymerization with organolithium proceeded in a living manner.…”
Section: Deprotonative Preparation Of the Monomer Species In Ht‐regiomentioning
confidence: 99%
“…It was revealed that Murahashi coupling polymerization was successfully achieved by the lithiated species of chlorothiophene, which is prepared by treatment of n BuLi and 5 . Following addition of nickel catalyst 20 underwent polymerization, where use of CPME (cyclopentyl methyl ether) as a solvent was found effective . Block copolymerization was also shown to take place suggesting that the polymerization with organolithium proceeded in a living manner.…”
Section: Deprotonative Preparation Of the Monomer Species In Ht‐regiomentioning
confidence: 99%
“…To date, only one NHC ligand has been used in CTP, with 2,6‐( i Pr) 2 C 6 H 3 substituents on the nitrogen atoms of the ring (abbreviated as IPr). Two Ni‐IPr precursors have been employed for the polymerization of thiophene monomers (Figure ) . Interestingly, three different cross coupling methods have been employed with this class of catalyst, demonstrating its broad potential in CTP.…”
Section: Nickel Catalysts In Ctpmentioning
confidence: 99%
“…Interestingly, three different cross coupling methods have been employed with this class of catalyst, demonstrating its broad potential in CTP. It has been explored for Murahashi, Kumada–Corriu and Suzuki–Miyaura coupling . In the recent report employing Ni(IPr)(PPh 3 )Cl 2 for ester functionalized thiophenes, the catalyst displayed some sensitivity to hydrolysis .…”
Section: Nickel Catalysts In Ctpmentioning
confidence: 99%
See 2 more Smart Citations